Telaah Terhadap Film Alif Lam Mim dan Kaitannya dengan Perspektif Aktivis Dakwah - Siti Rahmah; Syatibie Al Faroek (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2024)
This study aims to analyze the perception of da'wah activists on the da'wah values ??that exist in the film 3 Alif Lam Mim. And whether da'wah activists of STIDDI Al Hikmah Jakarta are aware of these issues, especially the problems of Islamophobia and pure secularism that marginalize religion. The method used is quantitative using multiple linear regression analysis. The conclusion of the study shows that the da'wah value variable influences the perception of da'wah activists of STIDDI Al Hikmah Jakarta. This means that da'wah activists perceive that there are da'wah values ??in the film 3 Alif Lam Mim, including the value of patience, the value of good morals and the value of steadfastness in worship that can be exemplified and applied by STIDDI Al Hikmah students as da'wah actors or da'i. The da'wah challenge variable influences the perception of da'wah activists of STIDDI Al Hikmah Jakarta. This means that da'wah activists perceive that there are da'wah challenges in the film 3 Alif Lam Mim, including Islamophobia, liberalism and secularism. However, da'wah activists perceive that this challenge can be countered by means of da'wah bil haal, da'wah bil lisan and da'wah bil hikmah. The variables of da'wah values ??and da'wah challenges together influence the perception of da'wah activists in watching the film 3 Alif Lam Mim. This is because the female da'wah activists of STIDDI Al Hikmah are in a da'wah campus environment that studies matters related to da'wah, both da'wah values ??and challenges, as well as the steps taken in dealing with da'wah problems